Minho robot football team - Machado, Carlos (2000)
Research and development in the robotics field can be greatly improved by attracting people with different challenges. RoboCup consists of a new challenge in which a team of robot players are supposed to play football with similar rules to the human football. This paper describes an Autonomous Mobile Robot Minho team solution. The robots were designed and developed by a group of undergraduate students from the Group of Automation and Robotics from the Industrial Electronics Department of the University of Minho, in Guimarães (Portugal). They were all built (electronics and mechanics) and programmed from scratch with a reduced budget. The main advantage of these robots consists on the image acquisition and processing. It uses a video camera pointing upwards to a convex mirror facing down. With this technique, most of the field is visible, facilitating the strategy of the game.